PENERAPAN METODE SMART PENENTUAN MEREK SIRUP TERBAIK PADA VUXIA BEAUTE CAFE - Agata, Akbar Kurnia; Hasugian, Humisar (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
Vuxia Beaute Cafe is a business in the beauty cafe industry established since September 2021. They always strive to ensure customer satisfaction by serving high-quality beverages. However, in running their business, they face challenges in determining the right syrup brand for their drinks. This is crucial because the syrup brand can influence the quality of the beverages they serve. Currently, the issue they are facing is the difficulty in finding a syrup brand that aligns with the customers' preferences and the lack of an effective procedure to objectively evaluate syrup brands. Currently, the evaluation of syrup brands is done subjectively based on the assessments of the cafe owner and head barista, making it challenging to determine the best syrup brand objectively. To address this problem, Vuxia Beaute Cafe needs a decision support system to assist in determining the best syrup brand based on the predefined criteria. In this research, the criteria used are taste, aroma, price, expiration date, and texture. The Simple Multi-Attribute Rating Technique (SMART) method was chosen because it is faster, simpler, and more effective in solving the problem. The data processing results indicate that the best syrup brand for Vuxia Beaute Cafe is Delifru with a score of 0.79, chosen based on the predefined criteria.